The Teacher Bandwidth Problem: MOOCs, Connectivism, and Collaborative Knowledge. Issue 4 (23rd November 2021) - Kotzee, Ben; Palermos, S. Orestis
Abstract : Massive Open Online Courses (MOOCs) have, in recent years, become increasingly popular. An important challenge facing MOOCs is the "teacher bandwidth problem ": in the MOOC environment, where there are potentially hundreds of thousands of students, it is impossible for a few teachers to interact with individual students — in other words, there is not enough "teacher bandwidth." According to George Siemens and Stephen Downes's theory of "connectivism, " one can make up for the lack of teacher bandwidth by relying on collaboration between students. Philosophically speaking, however, this theory is underdeveloped. In this paper, Ben Kotzee and S. Orestis Palermos consider the question of learner collaboration in online courses, and the theory of connectivism, from the perspective of social epistemology. They note the similarities between Siemens and Downes's theory and virtue reliabilist theories of epistemic collaboration more broadly. The paper has two main aims: first, to offer an illustration of how it is possible to conceptualize learner collaboration in online settings as analogous to collaboration between scientists; and second, to expand on and clarify what Siemens and Downes had in mind when they proposed the theory of connectivism.